Design of shaft boring machine control system - YANG Bingwen; FU Wenjun; LIU Zhiqiang (Gong-kuang zidonghua, 2016)
In order to ensure stable and reliable operation of shaft boring machine, an shaft boring machine control system based on PLC was designed, and composition, working principle and software and hardware design schemes were introduced. The system uses two PLC units to control corresponding oil pump, cutting bar rotating motor and pushing and supporting cylinder according to working mode, and uploads state parameters to local operation platform or remote controlling computer for display. The practical application shows that the system runs well.